Production Layout Planning Using Genetic Algorithms - Krajcovic, Martin; Hancinsky, Viktor (Communications - Scientific letters of the University of Zilina, 2015)
Globalisation of entrepreneurship has not only opened world markets but also global competition. The fundamental criteria for decisions on allocation of manufacturing capacities are currently not only costs (manufacturing, logistics, etc.), but mainly quality (of products, processes and services), flexibility (types of products, capacity, space, time) and a company´s innovative capability. Therefore the enterprise’s facility layout needs to be more flexible to adapt to the rapidly changing environment. The need for flexibility of layout planning puts higher requirements for utilisation of layout and location problem solving methods. Classical methods, like linear programming, dynamic programming or conventional heuristics are being replaced by advanced evolutionary algorithms, which give better solutions to large-scale problems. One of these methods are also genetic algorithms. This article describes the genetic algorithm utilisation in the production layout planning.